2023
DOI: 10.22270/jddt.v13i12.6267
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Different Approaches for Improving Curcumin Bioavailability

Saurabh D. Joshi,
Rohankumar Rajaram Chavan,
Asha S. Jadhav
et al.

Abstract: The creation and development of herbal nanoparticles have moved to the forefront of nanoformulation research. Curcumin is the most essential bioactive component of curcuma longa, a plant that has been utilized in traditional medicine for centuries. This chemical contains therapeutic properties that can be utilized to prevent and treat a wide range of ailments. Curcumin has proven therapeutic efficacy in the treatment of a range of human ailments, however, it has a limited bioavailability, which appears to be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Since Cu and R are known for their rapid metabolization when administered orally [90,91], in future research endeavors, it is crucial to explore the pharmacokinetics of Cu and R, with a particular emphasis on improving their solubility and bioavailability. Recent studies reported promising results when nanotechnology was used for developing new Cu and R delivery formulas [92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…Since Cu and R are known for their rapid metabolization when administered orally [90,91], in future research endeavors, it is crucial to explore the pharmacokinetics of Cu and R, with a particular emphasis on improving their solubility and bioavailability. Recent studies reported promising results when nanotechnology was used for developing new Cu and R delivery formulas [92][93][94].…”
Section: Discussionmentioning
confidence: 99%